Contextualizing Top-Down and Bottom-Up Approaches in Teaching Academic Listening at a Pesantren-Based University : - - Aries Fachriza; Nirmala Wulaningrum; Diska Fatima Virgiyanti; Dian Nashrul Munif Nashrul Munif (Darussalam English Journal (DEJ), 2025)
Listening is one of the essential skills in learning English. A person cannot speak or express their opinions without first listening. This research aims to identify the strategies used by lecturers in teaching listening and how these strategies are implemented. Specifically, this study investigates the application of top-down and bottom-up listening strategies. Top-down listening involves using prior knowledge, context, and background information to understand spoken language, while bottom-up listening focuses on decoding sounds, words, and grammatical structures to derive meaning. Understanding how lecturers incorporate these approaches can provide insights into effective listening instruction. This study employs a descriptive qualitative method using several instruments, including interviews and documentation. The participants in this study were students from the Department of English Language Education program at Darussalam Gontor University. The findings reveal that the lecturer employs an integrated three-stage approach—pre-, while-, and post-listening—while considering student factors. Pre-listening activates prior knowledge and top-down processing, while-listening combines top-down and bottom-up strategies, and post-listening enhances comprehension through interactive activities. Student motivation, interest, and participation play a crucial role in improving listening comprehension. These insights highlight the importance of a structured approach and learner engagement in teaching listening skills effectively